2013
DOI: 10.1002/app.40014
|View full text |Cite
|
Sign up to set email alerts
|

Bio‐oil from whole‐tree feedstock in resol‐type phenolic resins

Abstract: Renewable chemicals are of growing importance in terms of opportunities for environmental concerns over fossil-based chemicals. Lignocellulosic biomass can be converted into energy and chemicals via thermal and biological processes. Among all the transformation processes available, fast pyrolysis is the only one to produce a high yield of a liquid-phase product called bio-oil or pyrolysis oil. Bio-oil is considered to be a promising substitute for phenol in phenol formaldehyde (PF) resin synthesis. In this wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 22 publications
1
31
1
Order By: Relevance
“…The pH value of bio‐oil (3.5) was low because of the organic acids in the bio‐oil, but the pH value of BPF resin (11.16) was close to the value of the PF resin (11.53), which meant the acid in the bio‐oil had little impact on the synthetic reaction. The solid content of BPF resin was slightly lower than that of PF resin that might be justified by the high water content in the bio‐oil (31 wt%) . BPF resin had a lower bonging strength and larger formaldehyde emissions than PF resin, which was due to the relatively lower reactivity of phenols in bio‐oil compared with phenol towards aldehydes in the PF resin synthesis because of the steric hindrance, for example the ortho and para sites of the phenols in bio‐oil were already occupied by methoxy and carbonyl groups .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The pH value of bio‐oil (3.5) was low because of the organic acids in the bio‐oil, but the pH value of BPF resin (11.16) was close to the value of the PF resin (11.53), which meant the acid in the bio‐oil had little impact on the synthetic reaction. The solid content of BPF resin was slightly lower than that of PF resin that might be justified by the high water content in the bio‐oil (31 wt%) . BPF resin had a lower bonging strength and larger formaldehyde emissions than PF resin, which was due to the relatively lower reactivity of phenols in bio‐oil compared with phenol towards aldehydes in the PF resin synthesis because of the steric hindrance, for example the ortho and para sites of the phenols in bio‐oil were already occupied by methoxy and carbonyl groups .…”
Section: Resultsmentioning
confidence: 98%
“…However, phenol, one of the main raw materials in the synthesis of PF resin, is derived from petroleum‐based chemicals. The rising price of petroleum together with the scarcity of fossil feedstock and promoting environment‐friendly products have encouraged renewable resources . Hence, considerable efforts have been made to replace phenol partially with cheaper materials or renewable resources, such as urea , lignin , and plant oil .…”
Section: Introductionmentioning
confidence: 99%
“…The phenol replacement levels were 25%, 50%, and 75%, and the results obtained showed that the physical and mechanical properties of bio-based PF resins were strongly influenced by the substitution level of phenol. A substitution degree up to 50 wt% provided an equal or superior reactivity and performance to those of the pure PF resin (Chaouch et al, 2014). Mao et al investigated the feasibility of incorporating the bio-oil as part of a polymeric diphenylmethane diisocyanate (pMDI) binder system for flakeboard production.…”
Section: Application Of Phenolic-rich Bio-oilmentioning
confidence: 98%
“…[16][17][18][19] Bio-oil has been applied in the preparation of bio-oil-phenolformaldehyde (BPF) adhesives. [20][21][22][23][24][25][26][27][28][29] Some researchers have employed a mixture of phenol-formaldehyde (PF) and bio-oil to prepare BPF adhesives. [21][22][23][24] BPF adhesives are also prepared via the polycondensation method.…”
Section: Introductionmentioning
confidence: 99%
“…To solve this problem, some researchers have used a phenolization-polycondensation method to prepare highly substituted BPF adhesives. [26][27][28][29] Normally, when the bio-oil percentage is improved, the bonding performance of the highly substituted BPF adhesives will decrease.…”
Section: Introductionmentioning
confidence: 99%